BEVACIZUMAB FOR RETINAL VEIN OCCLUSION - Andrea Radotma Silitonga; Sindy boru Sembiring; Christina Josephina Bangun; Heri Purwoko (International Journal of Retina, 2020)
Introduction: Central retinal vein occlusion (CRVO) and branch retinal vein occlusion (BRVO) caused sudden visual decrease that most often treatable. This paper aims to describe clinical characteristic and outcome using bevacizumab for macular edema caused by retinal vein occlusion in real-life practice. Methods: This retrospective study included 91 treatment-naïve eyes with macular edema due to CRVO (55 eyes) and BRVO (36 eyes), who were treated with intravitreal bevacizumab (IVB) in pro re nata (PRN) regimen. Best corrected visual acuity (BCVA) and central macular thickness (CMT) before and after treatment were evaluated. Result: The mean age of patients was 60.3 + 11.2 years for CRVO and 55.7 + 8.2 years for BRVO. The mean baseline BCVA in the CRVO group was 1.41 + 0.55 logMAR. There was statistically significant improvement in BCVA after intravitreal bevacizumab compared to baseline (p < 0.001) in CRVO and BRVO group. Twenty six (47.3%) eyes with CRVO had BCVA > 1.0 logMAR (Snellen 20/200) at the last follow-up. In the BRVO group, the mean baseline BCVA was 0.93 + 0.48 logMAR. At the end of the follow up, 19 eyes (52.8%) with BRVO had BCVA > 0.3 logMAR (Snellen 20/40). There was also statistically significant improvement in CMT between all time points and baseline (p < 0.001) in both groups. At the end of the follow up, 26 (47.3%) eyes with CRVO and 25 eyes (69.4%) in BRVO group presented resolution of macular edema (CMT < 300). Conclusion: Intravitreal bevacizumab resulted in significant anatomical and functional improvement in macular edema associated with CRVO and BRVO, although outcome in CRVO group was sub-optimal.